Changing the load of a arrow crane while carrying out loading and unloading works - Sladkova L.A; Krylov V.V; Gorelova M.V. (Научно-технический вестник Брянского государственного университета)
The stability of self-propelled jib cranes is a key task in the process of their operation. The developed calculation scheme of the arrow self-propelled crane and the restrictions imposed on its movement in time and space, allowed to obtain mathematical dependence of the trajectory of the center of gravity of the arrow, a change in the speed of its movement at the arbitrary turn of the arrow, as well as cinematic and energy characteristics of the movement of cargo when combining operations during the operation of the crane. The combination of lifting and lowering cargo and a turn to the unloading place helps to increase productivity during the work of self-propelled jib cranes. Moreover, the full energy of the system (crane structure) depends not only on the position of the center of gravity of the arrow and cargo, but also on the angle of the arrow to the horizon. Moreover, the amount of full energy of the system is directly proportional to the angle of rotation in vertical and horizontal planes. The resulting theoretical dependence studies allow to determine the energy spent on lifting and lowering the load and the trajectory of its movement within the change of the angle of the arrow in the vertical plane.